Steroids in the dental implant osseointegration: literature review. - Neto, André Gaspar; Mascarenhas, Maria Luiza (Brazilian Journal of Implantology and Health Sciences, 2020)
Osseointegration of dental implants (OID) comprises the direct contact between bone and implant surface. Cyclooxygenase (COX) enzymes are essential in healing and cell regulation during bone repair and remodeling, being important in OID. Considering that non-steroidal anti-inflammatory drugs (NSAIDs) are COX inhibitors and commonly prescribed for relief of undesirable signs and symptoms in the postoperative period in implant dentistry, the present review aimed to study the influence of the use of these drugs in OID. For this purpose, the keywords Dental implantation, bone-implant interface and Anti-inflammatories, combined with each other and in the English language, were used in the Pubmed database. In all, 24 articles were found and, after reading their abstracts, 10 studies of pre-clinical (n = 6) or clinical (n = 4) scientific research were selected, which were read in full. Studies of literature reviews that did not use NSAIDs specifically were excluded. Among the 10 selected manuscripts, 5 studies found that NSAIDs interfere negatively in OID and all of these referred to selective or preferential COX 2 inhibition. Meanwhile, 2 studies found the opposite result, but using non-selective inhibitor NSAIDs and, therefore, of COX 1. The remaining 3 articles reported neutrality in the referred result. Thus, despite the lack of data in the literature, it is suggested that NSAIDs may interfere negatively in OID, especially as a result of COX-2 inhibition and in direct association with the dose of use.